Eggcellent Insights: Co-integration Analysis and Predictive Modeling across Production and Consumption Centers in India - , I. P. Deepak, J. Y. Premsagar, C. P. Gracy, G. Ranganath (Archives of Current Research International, 2025)
Growing demand for poultry products has captured the attention of market aspects of poultry industry. In this dynamic market, how well the market functionaries are operating, to what extend the price transmissions are captured and delivered to the stakeholders and such queries are vividly explained by this study. The daily wholesale prices of major egg markets, comprising production and consumption centers listed by National Egg Coordination Committee web portal, for a period of 486 days were taken for the study. Johansen’s co-integration test was applied to identify whether the spatially separated markets are co-integrated or not. Post analysis of unit root test by Augmented Dickey Fuller statistic, it is evident that the selected egg markets are co-integrated in the long run. While in the short run dynamics, the Vector Error Correction Model (VECM) explains the price transmission and speed of price adjustment among the egg markets. Granger’s causality test showed bidirectional influence of price among selected markets. The currently evolving Long Short-Term Memory (LSTM) model revealed that the model is viable in performing the predictions of future egg prices, but it does not coincide with the National Egg Coordination Committee (NECC) depicted prices. Further improvements could be focused on the egg price prediction process; which ultimately benefits all the stakeholders in this agribusiness.